Strategi Pembelajaran Pendidik dalam Meningkatkan Kompetensi Peserta Didik Abad 21 - Ahnan Hasan Marullah; Zaki Mubarok; Muhammad Ibnu Huda; Muhammad Abdullah Rizkiansyah (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2026)
This study aims to analyze educators' learning strategies to improve 21st-century student competencies in the digital era. The method used was library research, reviewing various books, journals, and research related to 21st-century learning. Data analysis was conducted descriptively and thematically, focusing on student characteristics, educator competencies, educational challenges, and innovative learning models. The results indicate that digital generation students are active, collaborative, and technologically engaged, requiring educators to integrate technology into their learning. Effective strategies include Project-Based Learning (PjBL), Problem-Based Learning (PBL), Flipped Classroom, Inquiry-Based Learning, and Blended Learning, which can enhance students' critical thinking, creativity, communication, collaboration, and digital literacy skills. oconclusion, the success of 21st-century learning depends on educators' ability to implement innovative, technology-based learning strategies tailored to student needs.